219k views
4 votes
Factorise : x^2+x-72 Step by Step​

2 Answers

3 votes

Answer:

x² + x - 72 = (x + 9)(x - 8)

Explanation:


x^2+x-72\quad \implies\quad a=1\,,\quad b=1\,,\quad c=-72\\\\x=(-b\pm√(b^2-4ac))/(2a)\\\\x=(-1\pm√(1^2-4\cdot1\cdot(-72)))/(2\cdot1)=(-1\pm√(1+288))/(2)=(17\pm√(289))/(2)\\\\x_1=(-1-17)/(2)=-9\quad,\qquad x_2=(-1+17)/(2)=8\\\\\\x^2+x-72=(x-(-9))(x-8)=(x+9)(x-8)

or:

x² + x - 72 =

= x² + 9x - 8x - 72 =

= x(x + 9) - 8(x + 9) =

= (x + 9)(x - 8)

User Atefth
by
5.4k points
2 votes

Answer:

(x + 9)(x - 8)

Explanation:

f(x) = x^2 + x - 72

= x^2 - 8x + 9x - 72

= (x^2 - 8x) + (9x - 72)

= x(x - 8) + 9(x - 8)

= (x + 9)(x - 8)

User StuStirling
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.